Molecular identification of common hard ticks (Acari: Ixodidae) in Xinjiang, China - Wang, Qiguo; Zhang, Yujiang; Sun, Surong; Luo, Tao; Mou, Wenting; Li, Bo; Dong, Xiao; Zhang, Xiaobing; Baokaixi, Guliayi; Cui, Yan (Zootaxa, 2021)
We provide data on the cytochrome c oxidase subunit I (COI) and 16S rDNA genes for eight species of common hard ticks in Xinjiang: Dermacentor montanus, D. niveus, Haemaphysalis sulcate, Hyalomma asiaticum asiaticum, Hya. detritum, Hya. scupense, Rhipicephalus sanguineus and R. pumilio. Genetic distances, calculated based on the Kimura two-parameter (K2P) distance model, found the same trend of intraspecies level≤interspecies level<intragenus level. Phylogenetic trees, constructed with the neighbor-joining (NJ) and minimum-evolution (ME) methods, demonstrated that each species clustered into separate clades, thus confirming the usefulness of CO1 and 16S rDNA genes for tick species identification. The genera Dermacentor, Haemaphysalis and Rhipicephalus were all recovered in the phylogenetic analysis, as was the subfamily Rhipicephalinae, but a monophyletic Hyalomma was not.